2010
DOI: 10.1039/c0jm00406e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of compositionally graded nanocast NiO/NiCo2O4/Co3O4 mesoporous composites with tunable magnetic properties

Abstract: Graphical contents entryMesoporous NiO/NiCo2O4/Co3O4 composites showing variable degrees of order and tunable magnetic properties are achievable by nanocasting using SBA-15 silica as hard templates. The -2 -NiCo2O4-rich powders are magnetic at room temperature and can be easily remotely manipulated using small fields (see Fig.).-3 -A series of mesoporous NiO/NiCo2O4/Co3O4 composites has been synthesized by nanocasting using SBA-15 silica as a hard template. The evaporation method was used as the impregnation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 42 publications
1
66
0
1
Order By: Relevance
“…The lattice parameter, phase wt% and crystalline size are obtained from the Rietveld refinement of the XRD patterns, as listed in Table 2. Note that the value of phase wt% is quantitatively estimated using relative peak intensity ratio [36,37]. All the catalysts are classified into three different types of crystal structure according to the major phase in the sample: NiO based type (Nickel oxide and 33:67), NiCo2O4 based type (50:50, 67:33 and 75: 25) and Co3O4 based type (Cobalt oxide).…”
Section: Icp-aes and Bet Resultsmentioning
confidence: 99%
“…The lattice parameter, phase wt% and crystalline size are obtained from the Rietveld refinement of the XRD patterns, as listed in Table 2. Note that the value of phase wt% is quantitatively estimated using relative peak intensity ratio [36,37]. All the catalysts are classified into three different types of crystal structure according to the major phase in the sample: NiO based type (Nickel oxide and 33:67), NiCo2O4 based type (50:50, 67:33 and 75: 25) and Co3O4 based type (Cobalt oxide).…”
Section: Icp-aes and Bet Resultsmentioning
confidence: 99%
“…For the case of GNCC-250, some NiO is also present, which would necessitate the formation of Co 3 O 4 . NiCo 2 O 4 and Co 3 O 4 are isostructural, so it is difficult to distinguish between the two phases based on XRD analysis [47]. Therefore, all three phases may coexist in the GNCC-250 specimen.…”
Section: Graphene-nickel Cobaltite Composite Electrodementioning
confidence: 99%
“…[ 5 ] The bulk NiCo 2 O 4 , nanorod NiCo 2 O 4 , and 3 wt% NiO/97 wt% NiCo 2 O 4 nanocomposite have been found to exhibit strong magnetization with a high saturation magnetization (M s ) of 29, ≈26, and 24 emu g −1 , respectively. [25][26][27] On account of these intrinsic properties and other advantages such as their low cost, rich abundance, and environmental friendliness, NiCo 2 O 4 materials have been extensively used in the fi elds of photodetection, [ 28 ] photocatalysis, [ 18 ] supercapacitors, [ 29 ] Li-ion batteries [ 30 ] and metal-air batteries, [ 31 ] fuel cells, [ 32 ] magnetic devices, [ 33 ] fl at-panel displays, [ 12 ] ferrofl uid technologies, [ 34 ] drug delivery, [ 35 ] optical limiters and switches, [ 36 ] infrared transparent conducting materials, [ 24 ] heterogeneous catalysis, [ 16 ] and various electrochemical reactions, for example: Cl 2 evolution, [ 37 ] O 2 evolution (OER), [ 38 ] O 2 reduction reaction (ORR), [ 39 ] H 2 O 2 reduction, [ 40 ] methanol oxidation, [ 41 ] and electrochemical sensors. [ 42 ] The extensive applications of NiCo 2 O 4 has encouraged the exploration of precise syntheses of particular NiCo 2 O 4 nanostructures.…”
Section: Introductionmentioning
confidence: 98%
“…[ 23 ] The magnetic properties and saturation magnetization of NiCo 2 O 4 can also be tuned by annealing, [ 24 ] morphology, [ 25 ] and components. [ 26 ] Iliev and co-workers have reported that epitaxial NiCo 2 O 4 fi lms deposited at temperatures lower than 450 °C are ferrimagnetic, and those grown at elevated temperatures are nonmagnetic. [ 5 ] The bulk NiCo 2 O 4 , nanorod NiCo 2 O 4 , and 3 wt% NiO/97 wt% NiCo 2 O 4 nanocomposite have been found to exhibit strong magnetization with a high saturation magnetization (M s ) of 29, ≈26, and 24 emu g −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%